Erosion Prediction and Soil Conservation Techniques In The Alue Geudeubang Sub Wstershed North Aceh Regency: PREDIKSI EROSI DAN TEKNIK KONSERVASI TANAH DI SUB DAS VALUE GEDUNG KABUPATEN ACEH UTARA - Andriyana; Halim Akbar; Khusrizal (ROCE : Jurnal Pertanian Terapan, 2024)
Erosion is the process of soil or soil particles being moved from one place to another by water. In the context of a watershed, erosion is a significant issue because it reduces soil productivity and increases sedimentation, thus reducing the lifespan of reservoirs. The goal of this research is to assess the predictive value of erosion in the Alue Geudubang Sub-watershed, North Aceh Regency. The research methodology involves a survey which includes a preparation stage, preliminary survey, main survey, data analysis, and presentation of results. Erosion prediction is calculated using the Universal Soil Loss Equation (USLE). The research findings indicate that the highest erosion prediction value is at SPL 10, where low-density mixed garden land, 0-8% slope, and Inceptisol soil type result in a value of 327.57 tonnes/ha/yr (ETol = 26.78 tonnes/ha/yr). Meanwhile, the lowest erosion prediction value is found at SPL 1 with forest land use, 0-8% slope, and Ultisol soil type, yielding a value of 5.01 tonnes/ha/yr (ETol = 16.17 tonnes/ha/yr). The recommended soil conservation technique for SPL 10 is to improve cropping patterns, such as planting high-density patterns combined with creating plant beds, to reduce the erosion rate to 9.83 tonnes/ha/yr (ETol = 26.78 tonnes/ha/yr).